2008
DOI: 10.1134/s0006297908120018
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeted plastoquinone derivatives as tools to interrupt execution of the aging program. 1. Cationic plastoquinone derivatives: Synthesis and in vitro studies

Abstract: Synthesis of cationic plastoquinone derivatives (SkQs) containing positively charged phosphonium or rhodamine moieties connected to plastoquinone by decane or pentane linkers is described. It is shown that SkQs (i) easily penetrate through planar, mitochondrial, and outer cell membranes, (ii) at low (nanomolar) concentrations, posses strong antioxidant activity in aqueous solution, BLM, lipid micelles, liposomes, isolated mitochondria, and cells, (iii) at higher (micromolar) concentrations, show pronounced pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
278
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(298 citation statements)
references
References 54 publications
19
278
0
1
Order By: Relevance
“…SkQ treatment normalised H 2 O 2 levels in HF+SkQ mice to those of the LF controls (Fig. 2c), thus confirming the efficacy of the mitochondrial-specific ROS scavenger as shown above and previously reported [12][13][14]. In addition, SOD2 (the mitochondrial SOD) activity was significantly elevated in HF mice (twofold vs LF, p<0.01) (Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…SkQ treatment normalised H 2 O 2 levels in HF+SkQ mice to those of the LF controls (Fig. 2c), thus confirming the efficacy of the mitochondrial-specific ROS scavenger as shown above and previously reported [12][13][14]. In addition, SOD2 (the mitochondrial SOD) activity was significantly elevated in HF mice (twofold vs LF, p<0.01) (Fig.…”
Section: Resultssupporting
confidence: 88%
“…SkQ is a small cationic molecule that targets and accumulates in the inner mitochondrial membrane [12]. SkQ mainly scavenges superoxide radicals arising from complex I, but can also sequester ROS generated from complex III [13], thus preventing excessive production of mitochondria-generated ROS. In vitro studies have shown that SkQ has a wide concentration range of antioxidant capacity [13], and in vivo studies have demonstrated that SkQ treatment effectively reduced oxidative damage in several models of oxidative stress [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In studies with a fungus, a crustacean, a fly, a fish, and mice, SkQ1 was shown to increase median lifespan (2,14). This effect was accompanied by retardation of the development of many age-related diseases and traits (2,14,(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Therefore, we searched for mitochondria-targeted antioxidants with wider antioxidant concentration "window" than that of MitoQ. Cationic derivatives of plastoquinone (SkQs) were found to have the desired property (2,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation